The knowledge, attitudes and practices of healthcare workers on drug hypersensitivity reactions in children: A tertiary centre experience from Turkey. Issue 9 (23rd June 2021) - Ercan, Nazli; Konukbay, Dilek
Abstract: Introduction: Adverse drug reactions are an important public health concern that affects doctor and dentist prescriptions and healthcare workers' practice. We planned to evaluate the knowledge, attitudes and practices of healthcare workers in our country about drug hypersensitivity reactions in paediatric patients and to determine the risk factors that may affect them. Method: This study was carried out in a capital‐located university hospital. Healthcare workers authorized to intervene in children (0‐18 age group), including medical doctors, nurses, and dentists, were enrolled in the study. The study questionnaire was developed by paediatric allergy and immunology specialists and paediatric nurses by considering the other studies on the same subject. Results: Three hundred fifty‐four (88.5%) out of 400 healthcare workers, whose study survey was distributed, returned to us by filling the questionnaire. According to the groups of the profession, there was a statistically significant difference between the average of correct answers given to the questions evaluating knowledge levels ( P < .001). The doctors' knowledge score ( M ± SD 18.6 ± 2.1) was the highest. The general attitudes of healthcare workers towards drug hypersensitivity reactions in children were similar and were positive ( P < .053). However, general practice patterns were significantly different ( P < .001). Nurses were observed to practice more positively than doctors and dentists. As the healthcare worker gets older, his practice score increased by 0.546; on the other hand, being a resident reduced the score from the practice score by 3.770. Conclusion: Our results suggest that advanced training programmes must be provided for healthcare workers in learning drug hypersensitivity reactions, particularly in paediatric patients.